Inactivation of classical and alternative pathway-activated bactericidal activity of human serum by sodium polyanetholsulfonate. - Traub, W H (1977)
Sodium polyanetholsulfonate (SPS) at a final concentration of at least 250 microng/ml (0.025%) was required for inhibition of the bactericidal activity of 80% (vol/vol) of fresh human serum against "promptly serum-sensitive" strains of Serratia marcescens and control strain Escherichia coli C, i.e., for inhibition of the classical pathway of complement activation. In contrast, SPS at 125 microng/ml (0.0125%) was sufficient for neutralization of the bactericidal activity of 80% (vol/vol) fresh human serum against "delayed serum-sensitive" strains of S. marcescens known to activate the alternative pathway of human complement. Addition of up to 500 microng of SPS per ml to 80% (vol/vol) fresh human serum failed to neutralize transferrin-mediated, "late" bacteriostasis against control strain E. coli C, an effect that was demonstrable only after prolonged, i.e., overnight, incubation of the test strain. However, this late inhibitory effect against E. coli C was not observed in SPS-treated 20% (vol/vol) fresh human serum or in 10 or 20% (vol/vol) conventionally heat-inactivated human serum. Immunoelectrophoretic examination disclosed that SPS did not precipitate transferrin from either fresh or heat-inactivated human serum. Thus, SPS, at 250 microng/ml, was demonstrated to be sufficient for the inhibition of both classical and alternative complement pathway-activated bactericidal activity of 80% (vol/vol) human serum. However, SPS at a concentration of 500 microng/ml failed to antagonize one antimicrobial system of 80% (vol/vol) human serum, namely transferrin-mediated bacteriostasis.